Faithful to the context? The presentation and representation of American objects in European collections (Anuário Antropológico, 2018)
In an exhibition entitled ART/artifact, which could be seen in various US museums between 1988 and 1990, objects from Africa were displayed in a variety of museum settings and installation styles (Exhibition Catalogue New York 1988). Some were given an overtly aesthetic presentation as a sculptural group in a way that was familiar to those who visit collections of modem sculpture in museums of modem art. Others were given individual treatment, presented under plexiglass and sanctified by spotlights. For instance, by displaying a repoussé’brass head made in the royal court of Abomey (Benin) lying on its side, it could be made to evoke works like Brancusi’s Sleeping Muse. The elongated stalks of three ivory hatpins from Zaire could be regarded as an abstract sculpture or a graceful plant, though their original audience saw them as neither. A pointed bark cloth hat from Zaire could become an effective sculpture under the photographer’s spotlights, arguably looking more interesting than when it was on someone’s head.